Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Different effects of prenatal air pollution exposure on cord blood protein profiles and postnatal lung function in infants born to asthmatic mothers - Carla Rebeca Da Silva Sena; Olga Gorlanova; Noëmi Künstle; Gabriela Martins Costa Gomes; Andrea Marten; Sven Schulzke; Florian Wyler; Vanessa E. Murphy; Paul D. Robinson; Peter D. Sly; Jakob Usemann; Benjamin Stoecklin; et al. (Environmental Research, 2026)

Co-production of low technical readiness level climate science through prototyping with users. Prospects in a European case study - E. Delpiazzo; K. Bülow; E. Baulenas Serra; C. Teichmann; J.H. Christensen; D. Matte; D. Bojovic; P. Kalverla; B.B. B. Booth; C.R. Goddard; F. Fung; B. Solaraju-Murali; et al. (Environmental Science & Policy, 2026)

Introducing Precision Medicine into an Undergraduate Medical Curriculum: An Interactive Lecture and Case-Based Learning Activity - Mara Rao; Christin Traba; Joshua Kra; Malcolm D. Mattes (Journal of Cancer Education, 2026)
Precision Medicine (PM)–the use of genomic, environment, and lifestyle data to design care based on individual patient characteristics–has become increasingly important in oncology practice. However, many medical schools lack dedicated instruction in this area. This study aimed to develop a novel educational session integrating PM into the Rutgers New Jersey Medical School third-year curriculum. An in-person, 1.5-h session was implemented, consisting of a lecture introducing definitions, diagnostic and therapeutic platforms, and challenges in PM, followed by an interactive clinical case discussing its applications in non-small cell lung cancer. Pre- and post-assessments evaluated students’ perceived abilities and attitudes and their knowledge and application of PM concepts. The session was attended by 178 students, with 136 paired pre- and post-tests available for analysis (pre-test response rate 92%, post-test 78%). After the session, students believed that they had a greater ability to apply PM in clinical scenarios (pre-test mean 2.7/5, post-test mean 4.3/5, p < 0.01) and perceived greater importance of learning about PM (pre-test mean 3.7/5, post-test mean 4.4/5, p < 0.01). Responses also showed modest improvement in objective content scores (pre-test mean 2.9/10, post-test mean 4.8/10, p < 0.01). At the end of the session, over 90% of students reported that they planned to apply what they had learned in their future practice of medicine. Overall, the session was effective in increasing participants’ understanding, confidence, and appreciation of PM. Future efforts should explore broader integration of PM content into curricula to better prepare students for its growing role in clinical practice.

A Compendium of Clinical, Research, Mentorship, and Education Opportunities in Radiation Oncology for Medical and Premedical Students - Joshua Y. Qian; Malcolm D. Mattes (Journal of Cancer Education, 2025)

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

Assessment of a Medical Student–Run Multidisciplinary Oncology Shadowing Program - Marco Santos Teles; Shrey B. Shah; Malcolm D. Mattes (Journal of Cancer Education, 2025)
Clinical exposures during the first two years of medical school (MS1-2) provide students an opportunity for early networking, mentorship and career exploration. The feasibility and perceived value of an extracurricular, student-run multidisciplinary oncology shadowing program was evaluated in this study. At a single institution, an oncology interest group collaborated with oncologists to create a shadowing program for MS1-2 students. Three radiation oncology (RO), two medical oncology (MO), and four surgical oncology (SO) faculty participated. A quarterly sign-up form was emailed to all MS1-2 students with available shadowing sessions. Electronic surveys were sent to students (after shadowing) and faculty (after 18 months of program operation) with multiple choice and 5-point Likert-type (1 = low, 5 = high) questions about their experiences. A total of 57 of the 97 participating students, and all 9 of the 9 participating faculty, responded to surveys (response rates 59% and 100%, respectively). Thirty students (53%) shadowed in RO, 23 (40%) in SO, and 4 (7%) in MO. Most students were very satisfied with their interactions with faculty (mean Likert-type rating of 4.14 ± standard deviation 0.85) and their overall experience compared to prior shadowing experiences (3.84 ± 0.85). Fifty-four students (96%) would recommend the experience to a classmate. Four faculty (44%) reported much more shadowing than before. Seven faculty (78%) felt the experience was best when residents or fellows were also present. All physicians planned to continue participating. This study demonstrated that a student-run, oncology shadowing program was feasible to implement, and viewed favorably by faculty and student participants.

Investigation of 3D circulation and secondary flows in the St. Lawrence fluvial estuary at a tidal junction - M. Le Mouel; P. Matte; A. Hammouti; D. Pham Van Bang (Estuarine, Coastal and Shelf Science, 2025)

Analysis of Oncology and Radiation Therapy Representation on the National Board of Medical Examiners Official Practice Material for the United States National Standardized Medical Board Examinations - Mary T. Mahoney; Lauren C. Linkowski; Trudy C. Wu; Jie Jane Chen; Beth K. Neilsen; Petria S. Thompson; Michael D. Mix; Karna T. Sura; Malcolm D. Mattes (Journal of Cancer Education, 2025)
Radiation therapy (RT) is a critical component of multidisciplinary cancer care, but has inconsistent curricular exposure. We characterize the radiation oncology (RO) content on the standardized undergraduate medical examinations by comparing its context and prevalence with other domains in oncology. National Board of Medical Examiners (NBME) self-assessments and sample questions for the United States Medical Licensing Exam (USMLE) Steps 1–3 and NBME clinical science shelf examinations were accessed ( n = 3878). Questions were inductively analyzed for content pertaining to oncology and treatment modalities of RT, systemic therapy (ST), and surgical intervention (SI). Questions were coded using USMLE Physician Tasks/Competencies and thematic analysis. Descriptive statistics and analyses using the Kruskal–Wallis test are reported. A total of 337 questions (8.6%) within the USMLE and shelf exams included oncology content, with 101 questions (2.6%) referencing at least one cancer treatment modality ( n = 35 RT, 45 ST, 57 SI). Treatment questions were more common on USMLE Step 2 CK ( n = 35/101, 32%) compared to Step 1 ( n = 23/101, 23%) and Step 3 ( n = 8/101, 8%) ( p < 0.001). RT was significantly less likely to be the correct answer (2/35, 6%) compared to ST (4/45, 9%) and SI (18/57, 32%) ( p = 0.003). Therapeutic oncology questions are uncommon on the examination material, with an under-representation of radiation-related content, and contextual bias favoring surgical approaches. We advocate for greater RO involvement in the content creation of such examinations to help trainees better understand multidisciplinary cancer care.

Promoting best practices in ocean forecasting through an Operational Readiness Level - E. Alvarez Fanjul; S. Ciliberti; J. Pearlman; K. Wilmer-Becker; P. Bahurel; F. Ardhuin; A. Arnaud; K. Azizzadenesheli; R. Aznar; M. Bell; L. Bertino; S. Behera; et al. (Frontiers in Marine Science, 2024)
Predicting the ocean state in a reliable and interoperable way, while ensuring high-quality products, requires forecasting systems that synergistically combine science-based methodologies with advanced technologies for timely, user-oriented solutions. Achieving this objective necessitates the adoption of best practices when implementing ocean forecasting services, resulting in the proper design of system components and the capacity to evolve through different levels of complexity. The vision of OceanPrediction Decade Collaborative Center, endorsed by the UN Decade of Ocean Science for Sustainable Development 2021-2030, is to support this challenge by developing a “predicted ocean based on a shared and coordinated global effort” and by working within a collaborative framework that encompasses worldwide expertise in ocean science and technology. To measure the capacity of ocean forecasting systems, the OceanPrediction Decade Collaborative Center proposes a novel approach based on the definition of an Operational Readiness Level (ORL). This approach is designed to guide and promote the adoption of best practices by qualifying and quantifying the overall operational status. Considering three identified operational categories - production, validation, and data dissemination - the proposed ORL is computed through a cumulative scoring system. This method is determined by fulfilling specific criteria, starting from a given base level and progressively advancing to higher levels. The goal of ORL and the computed scores per operational category is to support ocean forecasters in using and producing ocean data, information, and knowledge. This is achieved through systems that attain progressively higher levels of readiness, accessibility, and interoperability by adopting best practices that will be linked to the future design of standards and tools. This paper discusses examples of the application of this methodology, concluding on the advantages of its adoption as a reference tool to encourage and endorse services in joining common frameworks.

Considering sub-basins in the spatio-temporal dynamics of lake food webs - Jonathan J. Borrelli; Matthew S. Schuler; William D. Hintz; Brian Mattes; Candace Schermerhorn; Erika Yates; Lawrence W. Eichler; Mark A. Lucius; Laurie Ahrens; Rick A. Relyea (Aquatic Sciences, 2024)

Putting a lake together: Integrating synthetic data and field observations to build a better food web - Jonathan J. Borrelli; Matthew S. Schuler; William D. Hintz; Mary Alldred; Brian Mattes; Candace Schermerhorn; Erika Yates; Lawrence W. Eichler; Mark A. Lucius; Rick A. Relyea (Food Webs, 2023)

Evaluation of a Radiation Oncology Microclerkship as a Component of Medical Student Education - Shyamala Subramanian; Pranav Parikh; Joshua A. Kra; Pierre D. Maldjian; Susanne Walther; Sung Kim; Nicholas J. DeNunzio; Matthew J. Abrams; Steve E. Braunstein; Jillian R. Gunther; Malcolm D. Mattes (Journal of Cancer Education, 2023)

Phenotypically plastic responses to freshwater salinization in larval amphibians: Induced tolerance and induced sensitivity - Rick A. Relyea; Candace X. Schermerhorn; Brian M. Mattes; Isaac D. Shepard (Environmental Pollution, 2023)

Impact of air pollution on the health of the older adults during physical activity and sedentary behavior: A systematic review - Anderson D'Oliveira; Fábio Hech Dominski; Loiane Cristina De Souza; Joaquim Henrique Lorenzetti Branco; Darlan Lauricio Matte; Whyllerton Mayron da Cruz; Alexandro Andrade (Environmental Research, 2023)

Pilot Study Evaluating Cross-Disciplinary Educational Material to Improve Patients’ Knowledge of Palliative Radiation Therapy - Faryal Rizvi; Mark R. Korst; Meredith Young; Muhammad Hamza Habib; Joshua A. Kra; Ankit Shah; Tina M. Mayer; Biren Saraiya; Olga F. Jarrín; Malcolm D. Mattes (Journal of Cancer Education, 2023)

Pilot Study Demonstrating the Value of Interdisciplinary Education on the Integration of Radiation Therapy in Lung Cancer Management - Malcolm D. Mattes; Jason C. Ye; Gabrielle W. Peters; Faryal Rizvi; Tarita O. Thomas; Ravi A. Chandra; Elisabeth Weiss; Stanley I. Gutiontov; Sabin B. Motwani (Journal of Cancer Education, 2023)

Correction to: Diving ergospirometry with suspended weights: breathing- and fin-swimming style matter - Andreas Koch; Dennis Kramkowski; Mattes Holzum; Wataru Kähler; Sebastian Klapa; Bente Rieger; Burkhard Weisser; Jochen D. Schipke (European Journal of Applied Physiology, 2022)

Diving ergospirometry with suspended weights: breathing- and fin-swimming style matter - Andreas Koch; Dennis Kramkowski; Mattes Holzum; Wataru Kähler; Sebastian Klapa; Bente Rieger; Burkhard Weisser; Jochen D. Schipke (European Journal of Applied Physiology, 2022)
Purpose Scuba diving is a complex condition including elevated ambient pressure, limited air supply, increased breathing work, and unfamiliar fin-swimming. Earlier approaches to assess diving specific data did not comprehensively address these aspects. We first present an underwater ergospirometry system and then test the hypothesis that both breathing characteristics and fin-swimming style affect the air consumption. Methods/Participants A suspended-weights ergospirometry system was mounted inside a hyperbaric chamber. Ergo group: 25 divers (24.6 ± 4.1 years); three set-ups: dry normobaric cycling (75–225 W), dry cycling at 20 m simulated depth (75–225 W), fin-swimming at 20 m (5–8 kg suspended weights). Style group: 20 other divers (24.6 ± 4.1 years): fin-swimming at 20 m (5–8 kg) with regard to ventilation ( $$\dot{V}$$ V ˙ E) and fin-swimming style. Results Ergo group: linear heart rate and oxygen uptake ( $$\dot{V}$$ V ˙ O 2 ) increases with both 50 W-bicycle steps and suspended-weights ergometry ( r = 0.97). During hyperbaric conditions, $$\dot{V}$$ V ˙ E was less increased versus normobaric conditions. Style group: the more efficient hip/thigh-oriented style shifted towards the knee/calf-oriented style. $$\dot{V}$$ V ˙ E and $$\dot{V}$$ V ˙ O 2 were higher in beginners (< 100 dives) versus advanced divers (≥ 100 dives). Significant differences on the 5 kg-step: $$\dot{V}$$ V ˙ E: 31.5 ± 7.1 l/min vs. 23.7 ± 5.9 l/min and $$\dot{V}$$ V ˙ O 2 : 1.6 ± 0.3 l/min vs. 1.2 ± 0.3 l/min. A comparison is presented, in addition to illustrate the impact of differences in breathing characteristics and fin-swimming style. Conclusions Diving ergospirometry with suspended weights in a hyperbaric chamber allows for comprehensive studies. Little diving experience in terms of breathing characteristics and fin-swimming style significantly increases $$\dot{V}$$ V ˙ E thereby increasing the risk of running-out-of-air.

Comfort Level of US Radiation Oncology Graduates: Assessment of Transition to Independent Clinical Practice - Jeffrey V. Brower; Shuai Chen; Alex Ritter; Stanley L. Liauw; Stephen A. Rosenberg; Abhinav V. Reddy; Daniel W. Golden; Erin F. Gillespie; Malcolm D. Mattes (Journal of Cancer Education, 2021)

Effects of invasive larval bullfrogs (Rana catesbeiana) on disease transmission, growth and survival in the larvae of native amphibians - Andrew R. Blaustein; Devin K. Jones; Jenny Urbina; Ricky D. Cothran; Carmen Harjoe; Brian Mattes; Julia C. Buck; Randall Bendis; Trang Dang; Stephanie S. Gervasi; Rick Relyea (Biological Invasions, 2020)
The mechanisms by which invasive species negatively affect native species include competition, predation, and the introduction of novel pathogens. Moreover, if an invasive species is a competent disease reservoir, it may facilitate the long-term maintenance and spread of pathogens in ecological assemblages and drive the extinction of less tolerant or less resistant species. Disease-driven loss of biodiversity is exemplified by the amphibian–chytrid fungus system. The disease chytridiomycosis is caused by the aquatic chytrid fungus Batrachochytrium dendrobatidis (Bd) in anurans and is associated with worldwide amphibian population declines and extinctions. For amphibian species that metamorphose and leave infected aquatic habitats, the mechanisms by which Bd persists over winter in these habitats remains a critical open question. A leading hypothesis is that American bullfrogs ( Rana catesbeiana ), a worldwide invasive species, are tolerant to Bd and serve as a reservoir host for Bd during winter months and subsequently infect native species that return to breed in spring. Using outdoor mesocosms, we experimentally examined if two strains of Bd could overwinter in aquatic systems, in the presence or absence of bullfrog tadpoles, and if overwintered Bd could be transmitted to tadpoles of two spring-breeding species: Pacific treefrogs ( Pseudacris regilla ) and Cascades frogs ( Rana cascadae ). We found that only 4 of 448 total animals (one bullfrog and three spring breeders) tested positive for Bd after overwintering. Moreover, two of the three infected spring breeders emerged from tanks that contained overwintered Bd but in the absence of infected bullfrogs. This suggests that Bd can persist over winter without bullfrogs as a reservoir host. We found no effect of Bd strain on bullfrog survival after overwintering. For Pacific treefrogs, Bd exposure did not significantly affect mass at or time to metamorphosis while exposure to bullfrogs reduced survival. For Cascades frogs, we found an interactive effect of Bd strain and bullfrog presence on time to metamorphosis, but no main or interactive effects on their survival or mass at metamorphosis. In short, bullfrog tadpoles rarely retained and transmitted Bd infection in our experiment and we found limited evidence that Bd successfully overwinters in the absence of bullfrog tadpoles and infects spring-breeding amphibians.

Determination of structural factors affecting binding to mu, kappa and delta opioid receptors - Svetoslav Slavov; William Mattes; Richard D. Beger (Archives of Toxicology, 2020)

Student Perspectives on Oncology Curricula at United States Medical Schools - Brandon C. Neeley; Daniel W. Golden; Jeffrey V. Brower; Steve E. Braunstein; Ariel E. Hirsch; Malcolm D. Mattes (Journal of Cancer Education, 2019)

Computational identification of structural factors affecting the mutagenic potential of aromatic amines: study design and experimental validation - Svetoslav H. Slavov; Iva Stoyanova-Slavova; William Mattes; Richard D. Beger; Beat J. Brüschweiler (Archives of Toxicology, 2018)

Multiple microRNAs function as self-protective modules in acetaminophen-induced hepatotoxicity in humans - Dianke Yu; Leihong Wu; Pritmohinder Gill; William H. Tolleson; Si Chen; Jinchun Sun; Bridgett Knox; Yaqiong Jin; Wenming Xiao; Huixiao Hong; Yong Wang; Zhen Ren; et al. (Archives of Toxicology, 2018)

A Nationwide Medical Student Assessment of Oncology Education - Malcolm D. Mattes; Krishnan R. Patel; Lindsay M. Burt; Ariel E. Hirsch (Journal of Cancer Education, 2016)

The Evolving Role of Regional Radiation Oncology Societies in Resident Education - Malcolm D. Mattes (Journal of Cancer Education, 2015)

Model-guided therapy for hepatocellular carcinoma: a role for information technology in predictive, preventive and personalized medicine - Leonard Berliner; Heinz U Lemke; Eric vanSonnenberg; Hani Ashamalla; Malcolm D Mattes; David Dosik; Hesham Hazin; Syed Shah; Smruti Mohanty; Sid Verma; Giuseppe Esposito; Irene Bargellini; et al. (EPMA Journal, 2014)

Information and communication technology in personalized medicine: a clinical use-case for hepatocellular cancer - Leonard Berliner; Heinz U Lemke; Eric van Sonnenberg; Hani Ashamalla; Malcolm D Mattes; David Dosik; Hesham Hazin; Syed Shah; Smruti Mohanty; Sid Verma; Giuseppe Esposito; Irene Bargellini (EPMA Journal, 2014)

Summary of the workshop on methodologies for environmental public health tracking of air pollution effects - Thomas D. Matte; Aaron Cohen; Fred Dimmick; Jonathan Samet; Jeremy Sarnat; Fuyuen Yip; Nicholas Jones (Air Quality, Atmosphere & Health, 2009)

Production, purification and identification of fructooligosaccharides produced by β-fructofuranosidase from Aspergillus niger IMI 303386 - Quang D. Nguyen; Frank Mattes; Ágoston Hoschke; Judit Rezessy-szabó; Mahalingeshwara K. Bhat (Biotechnology Letters, 1999)

Lead exposure from conventional and cottage lead smelting in Jamaica - Thomas D. Matte; J. Peter Figueroa; Stephanie Ostrowski; Gregory Burr; Linnette Jackson-Hunt; Edward L. Baker (Archives of Environmental Contamination and Toxicology, 1991)